English for Specific Purposes - Shamsiddinovna, Ibragimova Dildora (The journal of contemporary issues in business and government, 2021)
English for architects is perhaps the most neglected kind of ESP (English for Specific Purposes). Architects need English for all kinds of reasons, and your first job as a teacher and/or course designer will be to work out what they are and which are priorities. The aims to find out the effectiveness of architectural drawings in teachingEnglish vocabulary . The media applied in the research worked in both improving Architecture-major students’ ability to learn the target language and motivating them in the teaching-learning process. A questionnaires analysis was used to determine factors affecting students’ lack ofEnglish vocabulary. The quasi-experimental method was applied to acquire the test data needed. Based on the analysis, the findings showed that there was a significant success on improving the students’ vocabulary mastery. However, as the architectural drawings used in the research were limited on the presentation type of drawing, other kinds of architectural drawings may not result in the similar way.